2022
DOI: 10.1158/1538-7445.am2022-3768
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 3768: Epigenetic dysregulation from chromosomal transit in micronuclei

Abstract: Chromosomal instability (CIN) and epigenetic alterations are characteristics of advanced and metastatic cancers, yet whether they are mechanistically linked is unknown. Here we show that missegregation of mitotic chromosomes, their sequestration in micronuclei, and subsequent micronuclear envelope rupture profoundly disrupt normal histone post-translational modifications (PTMs), a phenomenon conserved across humans and mice as well as cancer and nontransformed cells. Some of the changes to histone PTMs occur d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Surprisingly, another LEM-domain containing protein, LAP2α (Brachner & Foisner, 2014), was found with the same occurrence in both MN types (Fig.2C-D). Similarly, a lysine tri-methylation on histone H3 (H3K27me3), often enriched in MN (Agustinus et al , 2023), was also found with the same frequency in both MN types. Taken together, the collected data suggested that EMD level can differentiate MN into two fractions.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Surprisingly, another LEM-domain containing protein, LAP2α (Brachner & Foisner, 2014), was found with the same occurrence in both MN types (Fig.2C-D). Similarly, a lysine tri-methylation on histone H3 (H3K27me3), often enriched in MN (Agustinus et al , 2023), was also found with the same frequency in both MN types. Taken together, the collected data suggested that EMD level can differentiate MN into two fractions.…”
Section: Resultsmentioning
confidence: 95%
“…2C-D). Similarly, a lysine tri-methylation on histone H3 (H3K27me3), often enriched in MN (Agustinus et al, 2023), was also found with the same frequency in both MN types. Taken together, the collected data suggested that EMD level can differentiate MN into two fractions.…”
Section: Emd-rich Mn Differ In Composition From Mn With Emd-ne Levelsmentioning
confidence: 94%
“…This increases genomic instability, as shown by micronuclei accumulation. To identify these small DNA-containing cytoplasmic structures in vivo, we used known micronuclei markers such as DAPI/LAMIN A/C staining, γH2AX, and H3K27Me3 ( 33 , 34 ). Arid1a null hepatocytes show profound nuclear envelope malformations, characterized by the presence of deep invaginations, nuclear inclusions, and membrane bending and blebbing (fig.…”
Section: Resultsmentioning
confidence: 99%
“…First, we analyzed tumor DNA through WES or targeted exome sequencing, potentially masking the detection of sub-clonal populations with low abundance and limiting the analysis to the coding DNA regions. Copy number fluctuation of trans- and cis-intronic regulatory elements might also contribute to the evolution of TKI resistance in CDK4/6 amp, EGFRmt NSCLC and will be a subject of future analyses 49 . We also limited our investigation to canonical roles of CDK4/6 as cell cycle regulators, whereas their functions in regulating gene expression, cell metabolism and immune editing 50 will be further evaluated in expanded clinical cohorts, including other cancer types.…”
Section: Discussionmentioning
confidence: 99%